THEORETICAL AND METHODICAL ASPECTS OF SOIL DEGRADATION RESEARCH (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
The article provides an analysis of the theoretical position of land degradation. The commonality of factors contributing to degradation was revealed, and their model was developed. The article proposed a method for assessing the rate of degradation based on this model. The above-mentioned provides an opportunity to assess the degradation in any territory and develop measures to combat them.
Keywords: degradation; the extent of degradation; speed of degradation; the rate of degradation; number of compatibility; numerical value